Sprogpolitik: So ein Ding müssen wir auch haben - Bergenholtz, Henning; Bisgaard, Jonna; Lauridsen, Majken Brunsborg; Wichmann, Kamilla Kvist (HERMES - Journal of Language and Communication in Business, 2003)
To argue that language policies are subject to the vagaries of fashion may be a slight exaggeration. But language policies have indeed attracted growing interest and been increasingly debated over the last three to four years. During this time many companies and organisations have formulated a language policy, or they are currently in the process of doing so. At the national level several politicians have been complaining that no language policy exists for the Danish language. On the other hand, many journalists and several linguists have been criticising the language policy for which the Danish Language Council is responsible as inappropriate. All these statements may appear rather contradictory. The confusion can, however, partly be accounted for by the prevalence of different definitions of what a language policy is and what it involves. In this contribution we will suggest ways of resolving the terminological problems and also discuss some concrete Danish proposals for the part of language policy that we have termed ‘specific language policy’.